Hubungan Pendidikan dengan Pendapatan Orang Tua pada Balita Berstatus Gizi Buruk di Kecamatan Maesan Kabupaten Bondowoso - Siska Pradina; Samai Samai (Journal of Social and Political Science)
Malnutrition is a condition in which a person is declared to be in threshold (Z-Score) below average standard of < -3 Standard Deviation. Cases of toddlers with malnutrition status in Maesan Health Center, District of Maesan, Bondowoso Regency in 2013 increased when compared to those in 2012 which were found only on 7 toddlers, while started from January-June 2013 District of Maesan was still belonged to data listed in malnutrition cases which were found on 10 toddlers with malnutrition (Health Department of Bondowoso Regency 2012-2013). This research aimed to identify the relation between parents education and income on toddlers with malnutrition status in District of Maesan, Bondowoso Regency. This research used saturated sampling technique since there were 10 parents who had toddlers suffering from severe malnutrition. Data were collected using questionnaire, and then were analyzed using Spearman Rank Correlation analysis method with two-tailed test on significance level of 5% by t test. The results of the statistical test gained a value of -0.166 and a two-tailed test of 0.647. It showed that the value of rhostatistic was lower than that of rhotable (-0.166<0.648); this means that Ho was accepted and Ha was rejected, meaning that there is no relationship between parents education and income on toddlers with malnutrition status in District of Maesan, Bondowoso Regency. Keywords: education, income, parents, toddlers, malnutrition status.